Production of α-Amylase Inhibitors of Aspergillus RD2 from Dewandaru (Eugenia uniflora L.) as Diabetes Drug (Biosaintifika: Journal of Biology & Biology Education, 2022)
Diabetes mellitus is a metabolic disorder characterized by above normal blood glucose levels. A α-amylase inhibitors have inhibitory activity against α-amylase enzymes and cause decrease in glucose absorption. Dewandaru (E. uniflora L.) has the potential to produce compounds capable of controlling blood glucose levels. Aspergillus RD2 from twigs of the Dewandaru plant is expected to be able to produce antidiabetic compounds. This study aimed to determine the ability of the Aspergillus RD2 to produce α-amylase inhibitors by determining the production time, extracting α-amylase inhibitor compounds, testing the activity of the supernatant αα-amylase inhibitor and ethyl acetate extract with various concentrations of 2%, 4%, 6%, 8%, 10% and GC-MS analysis. The results showed the Aspergillus RD2 was able to produce αα-amylase inhibitors with an inhibitory activity of 59.71%. The incubation time of the Aspergillus RD2 in producing the highest α-amylase inhibitor was on the 7th day. The highest α-amylase inhibitor activity was at a concentration of 6% extract with an inhibition percentage of 82.79%. 9-Octadecenoic acid, 9-Octadecenal and n-Hexadecanoic acid were identified as having α-amylase inhibitor and antidiabetic activity. Aspergillus RD2 is able to produce α-amylase inhibitor compounds that have the potential to be used as antidiabetic drugs.